Vagueness and degrees of truth - Smith, Nicholas J. J. (Nicholas Jeremy Josef), 1972- (Oxford : Oxford University Press, 2008)
This text develops and defends a new position on vagueness. To make the book accessible to non-specialists, Nicholas Smith includes both an introduction to the relevant philosophical literature, and a gentle but thorough introduction to the required logical tools and concepts.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Vagueness (Philosophy); Truth